2019
DOI: 10.1111/hdi.12724
|View full text |Cite
|
Sign up to set email alerts
|

Is there a relationship between plantar foot sensation and static balance, physical performance, fear of falling, and quality of life in hemodialysis patients?

Abstract: Introduction: This study was conducted to investigate the relationship between plantar foot sensation and static balance, physical performance, fear of falling, and quality of life in hemodialysis patients. Materials and Methods: The study involved 24 hemodialysis patients and 20 healthy volunteers. Light touch‐pressure sensation (Semmes Weinstein Monofilament test kit), two‐point discrimination sensation (esthesiometer) and vibration sensation (128 Hz diapason) were used to evaluate plantar foot sensation. St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
(40 reference statements)
0
8
0
Order By: Relevance
“…The association between FOF and a history of falls was also found in patients with chronic obstructive pulmonary disease [20], patients with multiple sclerosis [21] and elderly patients [22]. Some factors that contribute to falls in patients on hemodialysis may explain the association between FOF and a history of falls in these patients, such as functional impairment, frailty and postural balance alterations [5,14]. In a recent study with 131 ESRD patients undergoing hemodialysis, it was observed that difficulty walking and frailty increased the chance of reporting high concern about falling by 4.74 and 2.47 times, respectively [5].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The association between FOF and a history of falls was also found in patients with chronic obstructive pulmonary disease [20], patients with multiple sclerosis [21] and elderly patients [22]. Some factors that contribute to falls in patients on hemodialysis may explain the association between FOF and a history of falls in these patients, such as functional impairment, frailty and postural balance alterations [5,14]. In a recent study with 131 ESRD patients undergoing hemodialysis, it was observed that difficulty walking and frailty increased the chance of reporting high concern about falling by 4.74 and 2.47 times, respectively [5].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study with 131 ESRD patients undergoing hemodialysis, it was observed that difficulty walking and frailty increased the chance of reporting high concern about falling by 4.74 and 2.47 times, respectively [5]. In another study with patients on hemodialysis, the authors observed an association between FOF, assessed by the FES-I, and postural balance and physical performance [14]. Moreover, Billis et al [23] observed lower FES-I scores in elderly people with one fall event than in those with two or more fall events in a 12-month interval (24.8 ± 5.3 vs. 31.1 ± 10.9), which demonstrates the relationship between the number of falls and FOF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Physiological and pathological aging related to this function increases the risk of falls [ 4 ]. Strong correlation between plantar sensation and static balance in hemiplegic patients has been previously suggested [ 5 ], and that stimulation of plantar sensation could improve static balance [ 6 ]. However, data on the therapeutic exercises that effectively improve this function remain limited.…”
Section: Introductionmentioning
confidence: 99%